Intensification of oxidative desulfurization of gas oil by ultrasound irradiation: Optimization using Box–Behnken design (BBD). (25th January 2017) - Jalali, Mohammad Reza; Sobati, Mohammad Amin
Highlights: Ultrasound-assisted oxidative desulfurization (UAOD) of gas oil was studied. The influences of the different operating parameters were investigated. Response surface methodology (RSM) was used to find the best operating parameters. An accurate correlation was developed for the sulfur removal. Ultrasound-assisted desulfurization process was compared with conventional process. Abstract: In the present work, ultrasound assisted oxidative desulfurization (UAOD) of gas oil as the feedstock with sulfur content of 2210 ppmw was investigated using a mixture of hydrogen peroxide and formic acid as the oxidant and catalyst, respectively. The influences of main process variables such as sonication time (2–30 min), oxidation temperature (40–70 °C), hydrogen peroxide to sulfur molar ratio (10–50), formic acid to oxidant molar ratio (2–4), ultrasound power per gas oil volume (5.56–8.89 W/mL), and number of extraction stages (1–4) on the sulfur removal of gas oil were investigated. Response surface methodology (RSM) based on Box–Behnken design (BBD) and single-factor experiments were employed. The best performance of UAOD process for gas oil was achieved at 50 °C of reaction temperature, oxidant to sulfur molar ratio of 46.36, formic acid to oxidant molar ratio of 3.22, sonication time of 19.81 min, and 7.78 W/mL as the ultrasound power per gas oil volume. The sulfur removal of UAOD process was evaluated after oxidation under the abovementioned conditions followed by (a) one stage extraction and (b) four stages extraction using acetonitrile as solvent. The observed sulfur removal was 87 for case (a) and 96.2% for case (b). The UAOD process was also compared with conventional ODS process. Considerable improvement on the sulfur removal was observed specially in lower reaction time in the case of using ultrasound irradiation in comparison with conventional mixing.